Activity of imipenem/relebactam against Pseudomonas aeruginosa with antimicrobial-resistant phenotypes from seven global regions: SMART 2015–2016. (December 2018) - Karlowsky, James A.; Lob, Sibylle H.; Young, Katherine; Motyl, Mary R.; Sahm, Daniel F.
Abstract: Objectives: Relebactam inhibits Ambler class A and C β-lactamases. Imipenem/relebactam has completed one phase 3 clinical study of patients infected with imipenem-non-susceptible Gram-negative bacilli. Two more phase 3 clinical studies are in progress for the treatment of patients with hospital-acquired and ventilator-associated bacterial pneumonia, complicated intra-abdominal infections and complicated urinary tract infections. In the current study, clinical Pseudomonas aeruginosa isolates cultured by medical centre laboratories in seven geographic regions (Africa, Asia, Europe, Latin America, Middle East, USA/Canada, South Pacific) were tested for susceptibility to imipenem/relebactam and comparators. Methods: A total of 12 170 isolates collected as part of the 2015–2016 Study for Monitoring Antimicrobial Resistance Trends (SMART) global surveillance program were tested using the Clinical and Laboratory Standards Institute (CLSI)-defined broth microdilution method. Relebactam was tested at a fixed concentration of 4 μg/mL in combination with doubling dilutions of imipenem. Imipenem/relebactam MICs were interpreted using current CLSI breakpoints for imipenem. Results: At the imipenem susceptible breakpoint (≤2 μg/mL), imipenem/relebactam inhibited 90.8% of all P. aeruginosa isolates and 70.7% of multidrug-resistant (MDR) isolates ( n = 3708). Relebactam restored imipenem susceptibility to 70.3% (2656/3776) of imipenem-non-susceptible isolates and increased percent susceptibility to imipenem against isolates with ceftazidime-non-susceptible (by 35.2%), piperacillin/tazobactam-non-susceptible (by 36.6%), cefepime-non-susceptible (by 36.8%) and MDR (by 41.9%) phenotypes. Across the seven geographic regions studied, susceptibility to imipenem/relebactam ranged from 84.0% (Latin America) to 96.0% (South Pacific). Conclusions: Imipenem/relebactam could provide an important treatment option against infections with P. aeruginosa isolates that are non-susceptible to several currently available antipseudomonal β-lactams. Highlights: Imipenem/relebactam inhibited 91% of Pseudomonas aeruginosa at the imipenem susceptible breakpoint (≤2 μg/mL). Susceptibility ranged from 84% in Latin America to 96% in South Pacific. Imipenem/relebactam inhibited 71% of multidrug-resistant P. aeruginosa isolates. Relebactam restored imipenem susceptibility to 70% of imipenem-non-susceptible isolates. Imipenem/relebactam could provide a treatment option for P. aeruginosa resistant to other antipseudomonal β-lactams.